Political Communication of Digital Banner in Chennai - NC, Krishna Priya (Journal of Advanced Research in Journalism & Mass Communication, 2018)
In the age of internet in states like Tamilnadu political communication is enacted primarily through medium like digital banners. In this context, studying political banners with political economy approach is relevant and important. The political economy studies, according to Vincent Mosco, also grew in response to the expansion of government as a producer, distributor, consumer and regulator of Communication. Masco’s concepts are relevant for this study and for the context of Tamilnadu as the state’s politics has a history of utilising media for political purposes, and more specifically state-owned production, distribution, consumption and regulation of communication. The Dravidian movement in Tamilnadu harnessed the potential of mass media for propaganda to propagate its ideology even before India was a free nation. At present, all the major political parties in the state own television channels and newspaper publications. Every new media has been appropriated and put to use by both ruling parties and the opposition parties, including digital banners. This paper examines the key characteristics of digital banner as a medium of communication in the city of Chennai using political economy approach. A cross section of the state holders including producers of the banner, owners of the digital banner units, workers, designers have been subjected to qualitative indepth interview. How to cite this article: Krishna Priya NC. Political Communication of Digital Banner in Chennai. J Adv Res Jour Mass Comm 2018; 5(4): 127-130.